2018
DOI: 10.3389/fmats.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials for Enhancing Neuronal Repair

Abstract: As they differentiate from neuroblasts, nascent neurons become highly polarized and elongate. Neurons extend and elaborate fine and fragile cellular extensions that form circuits enabling long-distance communication and signal integration within the body. While other organ systems are developing, projections of differentiating neurons find paths to distant targets. Subsequent post-developmental neuronal damage is catastrophic because the cues for reinnervation are no longer active. Advances in biomaterials are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 79 publications
(111 reference statements)
1
26
0
Order By: Relevance
“…In this study, both microscopic observation and FDA staining approved that the stem cells on <1 kPa substrate extended several dendrite-like processes with filopodiaenriched morphology and formed interconnected network structures. This result is in line with the findings of numerous studies which reported that the soft substrate can enhance neuritogenesis (Cangellaris & Gillette, 2018;Mosley et al, 2017) and it has been suggested that filamentous actin (F-actin) is the key factor in neuritogenesis whose organization is strongly regulated by substrate stiffness (Tanaka, Fujii, Kasai, Okajima, & Nakashima, 2018). In addition, our microscopic observations revealed that due to fast attachment of the cells to the softest surface, the mean cell area was higher compared to the CTRL group in the first hours of culture, but as cells attached to the stiff cell culture plate surface by 24 hr, they spread further and showed higher cell surface area compared to the soft one.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, both microscopic observation and FDA staining approved that the stem cells on <1 kPa substrate extended several dendrite-like processes with filopodiaenriched morphology and formed interconnected network structures. This result is in line with the findings of numerous studies which reported that the soft substrate can enhance neuritogenesis (Cangellaris & Gillette, 2018;Mosley et al, 2017) and it has been suggested that filamentous actin (F-actin) is the key factor in neuritogenesis whose organization is strongly regulated by substrate stiffness (Tanaka, Fujii, Kasai, Okajima, & Nakashima, 2018). In addition, our microscopic observations revealed that due to fast attachment of the cells to the softest surface, the mean cell area was higher compared to the CTRL group in the first hours of culture, but as cells attached to the stiff cell culture plate surface by 24 hr, they spread further and showed higher cell surface area compared to the soft one.…”
Section: Discussionsupporting
confidence: 93%
“…However, single neurotrophic factor is often not very effective ( Li et al, 2006 ; Cangellaris and Gillette, 2018 ). Various endogenous neurotrophic factors for nerve regeneration were reported ( Tajdaran et al, 2018 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is of special interest that the matrix is not only mechanically strong enough to withstand the pressure after implantation, but also deformable enough. 63 On one hand, the presence of keratin decreased the stiffness related to CHT membranes. On the other hand, its presence increased the capacity to disperse energy when subjected to a tensile force, by increasing the damping properties.…”
Section: Discussionmentioning
confidence: 99%